Research on computer using experience of primary school teachers in teaching of mathematics - Gesevičienė, Vilma (Lietuvos matematikos rinkinys, 2009)
The article deals with some questions of primary school teachers’ experience in using of informational and communicative technologies (ICT) and application of information technologies (IT) for practical development of schoolchildren’s mathematical abilities.